Value of electrocardiographic parameters and ajmaline test in the diagnosis of Brugada syndrome caused by SCN5A mutations. - Hong, Kui (2004)
BACKGROUND: The Brugada syndrome is an arrhythmogenic disease caused in part by mutations in the cardiac sodium channel gene, SCN5A. The electrocardiographic pattern characteristic of the syndrome is dynamic and is often absent in affected individuals. Sodium channel-blockers are effective in unmasking carriers of the disease. However, the value of the test remains controversial. METHODS AND RESULTS: We studied 147 members representing 4 large families with SCN5A mutations. Of these, 104 determined to be at possible risk for Brugada syndrome were selected for electrocardiographic and genetic evaluation. Twenty-four individuals displayed an ECG diagnostic of Brugada syndrome at baseline. Of the remaining, 71 received intravenous ajmaline. Of 35 positive genetic tests, 28/30 had Ajmaline positive, as opposed to 7/41 with negative Ajmaline test. The sensitivity, specificity, positive and negative predictive value of the drug challenge were 80% (28:35), 94.4%(34:36), 93.3%(28:30), and 82.9%(34:41) respectively. Penetrance of the disease phenotype increased from 32.7 to 78.6% with the use of sodium channel blockers. In the absence of ST segment elevation under baseline conditions, a prolonged PR interval, but not IRBBB or early repolarization patterns, indicate a high probability of an SCN5A mutation carrier. CONCLUSIONS: In families with Brugada syndrome, the data suggest that ajmaline test is valuable in the diagnosis of SCN5A carriers. In the absence of ST segment elevation at baseline, family members with first degree AV block should be suspected of carrying the mutation. Ajmaline test is often the key to making the proper diagnosis in these patients. SHORT ABSTRACT: The identification of SCN5A as responsible for Brugada syndrome allows validation of the diagnostic tools and electrocardiographic parameters used to identify the syndrome in patients with no ST segment elevation. We analyzed 4 families carrying different SCN5A mutations. Penetrance of the disease phenotype increased from 32.7 to 78.6% with the use of sodium blockers, with a sensitivity of 80% and specificity of 94.4%. First degree AV block suggests that a family member may be a carrier of the disease gene. The presence of IRBBB was not different among genetic carriers versus non-carriers. Clinicians should not rely in this parameter to suspect a positive diagnosis.